المذهب الظاهري وأثره في التصور النحوي لأبي حيان الأندلسي - جمال, عصام (University of Eloued جامعة الوادي, 2018)
ملخص هذا البحث يتناول أثر المذهب الظاهري في تصورات أبي حيان النحوية، وهو مذهب يأخذ بنصوص الكتاب و السنة على ظاهرها، ويعرض عن كل تأويل أو رأي أو قياس، وهو يعنى أساسا بمجال فقهي تبناه الفقهاء في تفسير النصوص الشرعية بعد أن أسسه أبو داود بن علي الأصبهاني بالعراق، ثم ما فتئ هذا المذهب أن تأفل شمعته - وذلك لجموده في مسائل وقف على ظاهرها - حتى أعيد إحياؤه بالأندلس على يد ابن حزم الأندلسي حتى لقب بالظاهري. وانتقل هذا المذهب من الفقه إلى النحو ليصير منهجا لغويا يعتمد على أسس وقواعد في تحليل ونقل المادة اللغوية إلى الأجيال وخاصة في مجال التعليمية ، وقد رأينا ابن مضاء كيف يثور على التراث اللغوي الذي تضخم بتقديرات و تأويلات وتعليلات وقياسات وشعب و فروع و أراء لا حصر لها ولاغنا، ونادى بإسقاطها، و الحفاظ فقط على المادة اللغوية المسموعة عن العرب والاكتفاء بها. كما وقفنا عند أراء أبي حيان وقارناها ببعض أصول الظاهرية، و وجدنا أنه تأثر بها فعلا، فقد نشأ في بيئة ظاهرية كان لها أثر في تكوين شخصيته الفكرية والعلمية، وقد كان يدعو بدوره إلى الابتعاد عن هذه التعقيدات و التأويلات التى زادت المادة النحوية ضخامة، وتسويدا للورق. وهذا يعني أن أبا حيان كانت له تصورات لا تختلف كثيرا عما شاع في بيئته، لولا أنه هاجر إلى المشرق وانقلب على بعض أصول المذهب الظاهري، فالظاهرية أسقطت مفهوم العامل في تفسير الجملة ودوره في نظام اللغة العربية، إلا أنه لم يكن يرى هذا الرأي، بل بالعكس تماما، فقد رأيناه يقر بالعامل النحوي ويذهب في ذلك مذهب القدماء من النحاة كسيبويه والخليل، ويقر بكل ما يذهب إليه هؤلاء الذين عدهم قدوته المثلى. Abstract :This research deals with the impact of the virtual doctrine in the perceptions of Abu Hayyan grammars, a doctrine that takes the texts of the Coran and the Sunnah on the face of it, and refuse about interpretation or opinion or measurement, It basically concerns a juristic field it was adopted by jurists in the interpretation of the texts of legitimacy after it was founded by Abu Dawood bin Ali al-Asbahani in Iraq, and then this doctrine continued to shine his candle - This is due to his freeze in matters of appearance cessation - Until he was revived in Andalusia by the son of Hazm Andalusi until the title of the virtual. And moved from the doctrine of jurisprudence to become a linguistic approach based on the foundations and rules in the analysis and transfer of linguistic material to generations, especially in the field of education. We have seen Ibn Moudaa how to revolt on the linguistic heritage, which inflated estimates, interpretations, interpretations, measurements, people and branches and opinions that are endless and Lagna, he called for its downfall, and to preserve only the linguistic material heard from the Arabs and sufficiency. As we stood at the views of Abu Hayyan and we compared it some of the assets of the virtual, and we found that he was really affected, it originated in a virtual environment that had an impact on the formation of its intellectual and scientific personality, he was in turn calling to stay away from these complexities and interpretations that increased the grammatical material immensity, and Squirting the paper. This means that Abba Hayyan had very different perceptions of what was common in his environment, had it migrated to the Orient and overturned some of the origins of the virtual doctrine, the Virtualism dropped the concept of the factor in interpreting the sentence and its role in the arabic language system, however, he did not see this view, but quite the opposite, we have seen it recognizes's of grammatical factor and go in that the doctrine of the ancients of the grammarians like a Sibaouih and Al Khalil, and recognizes's all that goes to who count they his best example.
مقال بمجلة الشهاب
Keywords: المذهب الظاهري ؛ أبو حيان ؛ابن مضاء ؛ القياس والسماع ؛ العامل ؛ التعليل